Jejunal atresia in the newborn: three cases after resection and end-to-end anastomoses - Ni Made Sukewanti; I Wayan Dharma Artana; Putu Junara Putra; I Made Kardana; Made Sukmawati; Kadek Deddy Ariyanta (DiscoverSys Inc., 2020)
Background: Intestinal atresia is a common cause of neonatal intestinal obstruction. Jejunal atresia occurs more frequent than duodenal or colonic atresias while single atresias are most commonly encountered. Jejunal atresia is classified into 4 types: Type I (a mucosal/septal), Type II (a fibrous cord/band), Type III (blind ends are entirely separated without a fibrous cord between them and a large mesenteric defect), and Type IV (combination of atresia type I to III). This study aims to elaborate jejunal atresia in the newborn after resection and end-to-end anastomoses.Case Description: We report three cases of jejunal atresia consists of different types: type IV (first case), type IIIa (second case) and type I (third case). Cases were neonates born with signs of upper gut obstruction. Bile-stained vomiting was reported a few hours after birth and failed to pass meconium in the first 24 hours. Postnatal abdominal X-ray showed dilatation of the gaster and no gas present in the pelvic floor. In the third case, it showed a triple bubble sign on abdominal x-ray and a laparotomy revealed the type of jejuno-ileal atresia. Also, the resection on the atresias and end to end anastomosis were performed. Cases were admitted to neonatal intensive care unit with total parenteral nutrition. The first two cases died due to sepsis, while the third case survived.Conclusion: Jejunal atresia is a rare disease among newborn. All of the patients have provided resection and end-to-end anastomoses, although 2 of them did not survive.